EMOSI TOKOH UTAMA DALAM CERPEN AL-YATIM KARYA MUSTHAFA LUTHFI AL-MANFALUTHI: PERSPEKTIF PSIKOANALISIS DAVID KRECTH - Siti Fatimah; Syarifuddin Syarifuddin; Irwan Mus; Azizah Nurmi’raj Amin (Universitas Negeri Makassar, 2025)
The purpose of this research is to classify emotions in the short story Al-Yatim using David Krech's literary psychology approach. This type of research is descriptive qualitative. The data collection method consists of literature study and reading and recording techniques. Data analysis was carried out through the stages of identification, classification, analysis, and conclusion of emotion data that appeared in the main character. The results showed six main classifications of emotions depicted in the main character, namely: alienation, loss, sadness, happiness, pent-up feelings, and love. These findings show the psychological complexity of the main character and demonstrate how emotions shape character and storyline. This research contributes to the development of literary psychology studies, especially the application of David Krech's emotion theory in character analysis. The results are expected to be a reference for similar studies in exploring the emotional dimensions of characters in literary works.